The Boondocks: Archetypes of Black Masculinity in a White World - Lafontant, Kworweinski (REDEN. Revista Española de Estudios Norteamericanos, 2022)
With American society being dominated and shaped by white men, black masculinity takes on new shapes and forms as black men seek survival within their surroundings. Through The Boondocks, a comic strip that has been syndicated into a TV show, five different archetypes of black masculinity take the spotlight through the main characters in a satirical world virtually void of black women in emphasis of the dynamics of black men. Huey is a revoluntionary, Riley is a Hip-Hop culturist, Grandad is a conformist, Tom is a traitor, and Uncle Ruckus is self-hating. No two methods to survival in white suburbia are the same, but what is shared is the collective need for the survival of the black community, in that the characters never stop looking out for each other regardless of the stark differences in how they express their black masculinity.